The association between physical activity and sleep in adult ADHD patients with stimulant medication use - Zhu, Feilong; Liu, Boya; Kuang, Dongqing; Zhu, Xiaotong; Bi, Xiaoyu; Song, Yiqi; Quan, Tianshen; Yang, Yiming; Ren, Yuanchun (Frontiers in Psychiatry, 2023)
Background: Adults with attention-deficit/hyperactivity disorder (ADHD) may experience sleep problems doubly suffering from disease and side effects of stimulant medications. Physical activity (PA) is known to produce numerous beneficial effects in adults. However, it was not well-characterized whether PA would still be effective in this situation. The main objective of the current study was to examine the relationship between PA and sleep among adult ADHD patients who were using stimulant medications and quantify the form of this association. Methods: Adult ADHD participants with stimulant medications use condition from the National Health and Nutrition Examination Survey (NHANES) database between January 1, 2013, and March 2020 (prepandemic) were included in the cross-sectional analysis. Weighted logistic regression was performed to assess relationship between PA level and sleep. A restricted cubic spline model was used to relax linear relationship assumptions and investigate associations between the risk of trouble sleeping and time spent engaging in moderate-to-vigorous PA per week. Results: A total of 162 eligible adult ADHD participants who reported using stimulant medicines were included. Participants who adhered to general recommendation of guidelines in the US of 150 minutes per week of moderate-to-vigorous PA had a significant lower risk of complaining of trouble sleeping (OR: 0.26, 95% CI: 0.10-0.67, p=0.006), and this association was seen in men (OR: 0.23, 95% CI: 0.09-0.56, p=0.002), but was not seen in women (OR: 0.71, 95% CI: 0.27-1.88, p=0.500). Restricted cubic spline analysis showed that the incidence of trouble sleeping gradually decreased after at least 105 minutes of moderate-intensity PA per week in participants (OR: 1.02, 95% CI: 0.92-1.14). A significant difference appeared after 341 minutes (OR: 0.87, 95% CI: 0.76-0.99), and the curve leveled after 1250 minutes (OR: 0.60, 95% CI: 0.46-0.79). Conclusion: Our findings observed associations between PA and sleep condition in the adult ADHD patients with stimulant medication use population. Moderate-to-vigorous PA may be beneficial to sleep in adults with ADHD who were using stimulants and thus should be recommended as part of a healthy lifestyle. Gender difference should be considered as an important factor for further studies to examine these associations and explore potential mechanisms.